PERSEPSI GURU TERHADAP PENGUASAAN ADVANCE MATERIALS UNTUK PEMBELAJARAN GEOGRAFI - Nandi, Nandi; Murtianto, Hendro; Pamungkas, Totok Doyo; Putri, Indri Megantara; Wijaya, Muhamad Akbar (Indonesia University of Education, 2020)
The ability to manage learning is a competency that must be possessed by a teacher, including geography teachers. Not only pedagogically, a geography teacher is expected to be able to convey geography learning contextually. To improve the capability of geography teachers during learning, it is necessary to increase the ability to master the materials by deepening advanced materials. This study was conducted to determine perceptions of mastery of advance materials for geography learning conducted to 142 geography teachers as respondents. This study is important given the lack of literature on the perception of geography teachers in mastering advanced materials. Based on the research results, the teacher conceptually understands what is meant by advance materials. This understanding can be seen at least from the teacher's ability to differentiate between advance materials and essential materials as well as teacher competence in sorting materials based on the depth of the materials.